Lung function and exhaled nitric oxide in healthy unsedated African infants - Gray, D.; Willemse, L.; Visagie, A.; Smith, E.; Czövek, D.; Sly, P.; Hantos, Z.; Hall, Graham; Zar, H. (Wiley-Blackwell Publishing Asia, 2015)
Background and objective: Population-appropriate lung function reference data are essential to accurately identify respiratory disease and measure response to interventions. There are currently no reference data in African infants. The aim was to describe normal lung function in healthy African infants. Methods: Lung function was performed on healthy South African infants enrolled in a birth cohort study, the Drakenstein child health study. Infants were excluded if they were born preterm or had a history of neonatal respiratory distress or prior respiratory tract infection. Measurements, made during natural sleep, included the forced oscillation technique, tidal breathing, exhaled nitric oxide and multiple breath washout measures. Results: Three hundred sixty-three infants were tested. Acceptable and repeatable measurements were obtained in 356 (98%) and 352 (97%) infants for tidal breathing analysis and exhaled nitric oxide outcomes, 345 (95%) infants for multiple breath washout and 293 of the 333 (88%) infants for the forced oscillation technique. Age, sex and weight-for-age z score were significantly associated with lung function measures. Conclusions: This study provides reference data for unsedated infant lung function in African infants and highlights the importance of using population-specific data.